Is there any effect of fenugreek seeds aqueous extract (FSA) on the quantity of ovarian follicles and estrus cycle of female rats…? - Allow, Ahmed Kaid Naji; Abdulmugni, Sadeeq; Ahmed Kaid, Belqees; Mohamed Bakrim, Norbaiyah; Yousof, Zainab; Hellis, Ayah; Al-Ani, Imad Matloub Dally; Mohd Hassan, Norazian; Bracamonte, Maryam; Mustafa, Imad Al-Deen (Everant Publisher, 2016)
Sixty healthy mature female rats were involved in this study to evaluate the potential effects of FSA extract on number of ovarian follicles and estrus cycle stages. The female rats were randomly divided into four groups of 15 rats/each. The first group A was the control was given distilled water; the B, C and D received 250, 500 and 1000 mg/kg FSA extract, respectively, for 21 days. A significant irregularity of estrus cycle, reduction in relative ovarian weights, reduction in the number of secondary follicles and corpora lutea in all treated groups and increase in the number of antral follicles in all treated groups in compared to the control. In conclusion, the observation of irregular estrus cycle, significant decrease in the number of secondary and antral follicles, and significant increase in the number of atretic follicles demonstrated the potential effects of fenugreek seeds.